2021
DOI: 10.3389/fspor.2021.635478
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness and Motor Competence in Upper Austrian Elementary School Children—Study Protocol and Preliminary Findings of a State-Wide Fitness Testing Program

Abstract: Motor competence and physical fitness are key components for the promotion of an active and healthy lifestyle. Poor motor competence and low physical fitness in children, therefore, are a major threat to future public health. Even though the assessment of physical fitness and motor competence per se does not enhance these entities, fitness tests can provide important information for intervention strategies. Fitness tests may also motivate children to become more active in order to increase their physical abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…This result is in line with previous research reporting no association of balance and muscular strength [89][90][91]. The ball-push test, on the other hand, is the only one out of the six tests in which overweight children outperform normal-or underweight children [70,71] and might thus be primarily an indicator of physical 'unfitness'. For further discussion of the role of weight status for test performance, we refer to Bähr et al [70] and Fühner et al [45].…”
Section: Source Of Variancesupporting
confidence: 91%
See 1 more Smart Citation
“…This result is in line with previous research reporting no association of balance and muscular strength [89][90][91]. The ball-push test, on the other hand, is the only one out of the six tests in which overweight children outperform normal-or underweight children [70,71] and might thus be primarily an indicator of physical 'unfitness'. For further discussion of the role of weight status for test performance, we refer to Bähr et al [70] and Fühner et al [45].…”
Section: Source Of Variancesupporting
confidence: 91%
“…In contrast to the present study, the Thuringian study also assessed the children's body mass index (BMI) and found that normal-weight third-graders, with a BMI of around 15, showed the highest pandemic-related drop in performance. This can be described as an inverse Matthew effect for children with a larger BMI, who tend to show a lower performance in most physical fitness tests than normal-and under-weight children [70,71]: They had less physical fitness to lose.…”
Section: Source Of Variancementioning
confidence: 99%
“…The study population consisted of 18,168 children between 6 and 11 years of age (mean age: 8.4 ± 0.8 years) that participated in a state-wide, school-based physical fitness assessment, which has been described in detail elsewhere [ 40 ]. The study procedures were in accordance with the 2008 declaration of Helsinki and the study protocol has been approved by the Upper Austrian school board as well as the participating schools.…”
Section: Methodsmentioning
confidence: 99%
“…PF is strongly related to body constitution, speci cally when assessed as some combination of the two readily available measures of height and mass [22][23][24] . The most widely used are BMI and HMR, but other indices based on height and mass with variations of power coe cients in their formulas have been proposed [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%